Na forma do estilo-normas da boa pena nos séculos XVII e XVIII em Portugal e Espanha - Almada, Márcia (Documenta & Instrumenta - Documenta et Instrumenta, 2010)
This article presents the analysis of some of the forms of apprenticeship and work used by writing professionals during the 17th and 18th centuries in the Iberian Peninsula, giving priority to the visual aspects of the texts. Clerks should master the rules, which were learned by doing or through printed or manuscript handbooks. From the treaties of Arte da Escrita (The Art of Writing) we can extract the rules current in each period of time, as many authors cared to clarify and spread the forms of production of a public document, from the grammatical correction to the page layout and choice of font. Writing is a cognitive, communicative and expressive tool. It therefore possesses certain sets of rules that must be followed in order to fulfill its purposes. Taking as example the public documents produced in the Western world during the Modern Era, we notice a pre-established constructive order: cartas de mercês (concession certificates), requisitions, diplomas, brotherhoods’ statutes, among others, should be executed “in the form of the style”. These rules concerned not only the text itself but also its aesthetic order. Certain types of fonts, supports and page layout were used according to the purpose, the sender or the addressee of the document and allow to notice, at first glance, its social function.
Keywords: Writing; Calligraphy; Teaching; 17th and 18th centuries